Organizational Culture and Employee Performance: Assessing the Influence on the Implementation of Public Services During The Covid 19 Pandemic - Widyawati Widyawati; Sulmiah Sulmiah; Nurlaela Nurlaela (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2021)
Public service providers during the COVID-19 pandemic face challenges in realizing quality services. At this time, service providers need the support of an organizational culture that is sensitive to change and optimal employee performance. Therefore, to determine the influence of organizational culture and employee performance in public services, this study is directed to analyze organizational culture and employee performance in supporting the implementation of quality public services in agencies engaged in public services in Central Mamuju Regency. In order to obtain objective research results, quantitative methods were used. Research data were obtained from questionnaires distributed to 102 samples, which were then strengthened by the results of interviews and secondary data related to the research topic. The results showed that the relationship between organizational culture and employee performance in influencing the quality of public service delivery during the COVID-19 pandemic was inseparable from the leadership and financial management factors of the organization. Leaders who cannot make decisions in favor of employees reduce employee work motivation. In addition, the use of applications as a solution for public service delivery during a pandemic cannot be utilized properly due to a lack of management budget. So that organizational culture and employee performance in public service agencies in Central Mamuju Regency cannot encourage the implementation of quality public services for the community during the COVID-19 period.